(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
Successful integration of Circular Economy (CE) within economic systems can significantly contribute to sustainable development by promoting economic growth through closed-loop systems. Nonetheless, despite CE principles aligning closely with the United Nations’ Sustainable Development Goals (SDGs), their integration into public policy faces limitations. This study adopts a qualitative research approach, drawing insights from academic literature and European legislation, so as to shed light on the challenges and barriers obstructing the effective implementation of CE principles within the framework of the EU. Focusing on regulatory obstacles, this research analyzes the intersection of Sustainability Economics (SE) with CE, identifies major CE principles and observes the challenges involved in incorporating them into public policy. It then reviews European Union (EU) milestones in adopting CE, under both the Juncker Commission and the von der Leyen Commission, and assesses the obstacles in integrating CE within EU public policy. The study found that major challenges highlighted in the literature include insufficient awareness, limited infrastructure for recycling and reusing materials, and ensuring collaboration between governments, industries, and consumers. Continuing to implement comprehensive policy frameworks is essential for promoting CE practices in the EU.